A Scaffold‐Hopping Strategy toward the Identification of Inhibitors of Cyclin G Associated Kinase. (2nd January 2019) - Wouters, Randy; Tian, Junjun; Herdewijn, Piet; De Jonghe, Steven
Abstract: We recently reported the discovery of isothiazolo[4, 3‐ b ]pyridine‐based inhibitors of cyclin G associated kinase (GAK) displaying low nanomolar binding affinity for GAK and demonstrating broad‐spectrum antiviral activity. To come up with novel core structures that act as GAK inhibitors, a scaffold‐hopping approach was applied starting from two different isothiazolo[4, 3‐ b ]pyridines. In total, 13 novel 5, 6‐ and 6, 6‐fused bicyclic heteroaromatic scaffolds were synthesized. Four of them displayed GAK affinity with K d values in the low micromolar range that can serve as chemical starting points for the discovery of GAK inhibitors based on a different scaffold. Abstract : A stop‐GAK approach : Starting from a cyclin G associated kinase (GAK) inhibitor based on an isothiazolo[4, 3‐ b ]pyridine skeleton, a scaffold‐hopping strategy was applied, resulting in the synthesis of 13 novel scaffolds. Four of these scaffolds (isothiazolo[3, 4‐ b ]pyrazine, pyrazolo[1, 5‐ a ]pyrimidine, imidazo[4, 5‐ b ]pyridine, and quinazoline) display potent GAK affinity with K d values <1 μm . These heterocycles can be used as starting points for the discovery of novel GAK inhibitors based on a different chemotype.